Quantitative characterization of damage and the cross-scale evolution mechanism of soft rock under dry-wet cycles - Liang, Ning; Jin, Tao; Su, Dingli (Frontiers in Earth Science, 2024)
Soft rock undergoes internal structural redistribution and random damage under the action of dry–wet cycles, with these processes ultimately affecting its mechanical properties. In order to analyze the evolution mechanism of mineral composition inside soft rocks, an effective method for the characterization of the nonlinear damage of soft rock using a multifractal spectrum is presented. Moreover, a cross-scale correlation model of internal structural changes and strength degradation is established. Based on scanning electron microscopy (SEM) images of soft rock subjected to a varying number of dry–wet cycles, the damage propagation path was tracked via a rock-like compression failure test. The study results indicate that soft rock exhibits a random fractal damage effect under the action of dry–wet cycles. As the number of cycles increases, the multifractal spectrum becomes more asymmetric and the discretization degree becomes more uneven. The soft rock exhibits cross-scale evolution characteristics from mesostructural to macroscopic damage after encountering water. After a series of reactions between water and soft rock, the bonding between particles weakens and recombines, ultimately affecting the mechanical properties of the soft rock. The research results have enriched the research framework of soft rock failure mechanisms, and provided an effective method for quantitatively characterizing the correlation analysis between soft rock damage and damage at different scales.